Reliability of electrical security systems in external protection of the military objects - Tatiana Olejnikova (Communications - Scientific letters of the University of Zilina, 2004)
In this paper electrical security systems used in military objects and areas of the Slovak Republic Armed Forces are described. There is described a method of reliability calculation of the safety system elements as a probability that the system will operate without a failure during the defined time in the given conditions.